The Mw 6.4 Damas, Costa Rica, Earthquake of 20 November 2004: Aftershocks and Slip Distribution - Pacheco, Javier F. (2006)
The earthquake of 20 November 2004 was located north of Damas Island in the Pacific coast of Costa Rica, within the Costa Rica Deformed Belt. The earthquake was located at 24 km depth and reported with a magnitude (Mw) of 6.4 and a strike-slip mechanism with a large normal dip-slip motion. This mechanism agrees with mapped faults in the area that suggest transtensional deformation on the forearc and the entire western boundary of the Panama microplate. Aftershock locations do not delineate a preferable plane to distinguish between the two nodal planes and are distributed between 15 and 25 km depth. The slip distribution during the mainshock, modeled after teleseismic and local data, pictured a circular rupture 8 km in radius and 0.25 m of average displacement. The fault plane cannot be distinguished from the two nodal planes from the slip distribution because of the lack of directivity and resolution for this magnitude earthquake. Weak evidence from empirical Green’s function analysis suggests that the dextral northwest-oriented fault could be the causative fault. Depth to the top of the slab, hypocenter location of the mainshock, its slip distribution, depth distribution of the aftershocks, and Quaternary fault activity at the surface suggest that deformation takes place throughout the whole thickness of the crust. This extended deformation might be caused by seamount subduction and strong basal friction on the upper plate, due to subduction of a thick, young, and buoyant oceanic plate, rough seafloor, and underplating of large seamounts.